The Effect of the Implementation of Government Accounting Standards, Human Resource Competencies, and Integrated Agency-Level Financial Application Systems as Determinants of the Quality of Government Financial Statements - Lia Puspasari; Cris Kuntadi (Journal of Accounting and Finance Management, 2023)
This article presents a review of the factors that influence the quality of government financial statements as the dependent variable on the implementation of Government Accounting Standards (SAP), Human Resources competencies, and Integrated Agency-Level Financial Application System (SAKTI) as independent variables. This article has a purpose as a hypothesis that builds influence between variables so that it can be used in further research. This article is a literature review that shows that there is an influence of the variable implementation of Government Accounting Standards on the variable quality of government financial statements, the influence of the variable Human Resources competence on the variable quality of government financial statements, and the influence of the variable implementation of the Integrated Agency-Level Financial Application System (SAKTI) on the quality of government financial statements.